Analisis Penerapan Normalisasi dan Mengurangi Redudansi Data pada Sistem Informasi Penjualan: Analysis of the Implementation of Normalization and Reducing Data Redundancy in Sales Information Systems - Bella Audya Manalu manalu; Muhammad Irwan Padli Nasution (Pendidikan Al-Gafari, 2026)
This study aims to analyze the application of database normalization as a solution to reduce data redundancy in sales information systems. Good data design is the foundation of an efficient and reliable sales information system. Data redundancy is a fundamental problem often encountered in sales information systems that have not implemented database normalization optimally, resulting in data duplication, transaction anomalies, information incoherence, and wasted storage capacity. Data were obtained through literature studies and document analysis from various sources relevant to the theme of data normalization and data redundancy. The results of the analysis show that the gradual application of normalization from Unnormalized Form (UNF) to Third Normal Form (3NF) and Boyce-Codd Normal Form (BCNF) has been proven to consistently reduce data redundancy, eliminate anomalies, and increase the efficiency of sales information systems. These findings provide a practical contribution in the form of a guide to implementing normalization for sales information system developers.